On the natural diversity of phenylacylated-flavonoid and their in planta function under conditions of stress - Tohge, Takayuki (Phytochem Rev, 2017)
Plants contain light signaling systems and undergo metabolic perturbation and reprogramming under light stress in order to adapt to environmental changes. Flavonoids are one of the largest classes of natural phytochemical compounds having several biological functions conferring stress defense to plants and health benefits in animal diets. A recent study of phenylacylated-flavonoids (also called hydroxycinnamoylated-flavonoids) of natural accessions of Arabidopsis suggested that phenylacylation of flavonoids relates to selection under different natural light conditions. Phenylacylated-flavonoids which are decorated with hydroxycinnamoyl units, namely cinnamoyl, 4-coumaroyl, caffeoyl, feruloyl and sinapoyl moieties, are widely distributed in the plant kingdom. Currently, more than 400 phenylacylated flavonoids have been reported. Phenylacylation renders enhanced phytochemical functions such as ultraviolet-absorbance and antioxidant activity, although, the physiological role of phenylacylation of flavonoids in plants is largely unknown. In this review, we provide an overview of the occurrence and natural diversity of phenylacylated-flavonoids as well as postulating their biological functions both in planta and with respect to biological activity following their consumption.